Pragmatic and Lingua-cultural Pasport of Persuasives конечно (of course), может быть (may be), кажется (it seems) - LAMBARJYAN, SRBUHI (Bulletin of Yerevan University H: Russian Philology, 2021)
The article is deroted to the analising of pragmatic and lingua-cultural aspects of modal operators конечно, может быть, кажется. Тhe research shows, that this persuasive realize different meanings in different contexts. The aim of the research – to describe some of these meanings.